The Relationship Between Organizational Culture and Administrative Creativity in Universities - Salama, Ibtisam Khalid Yahia (European Scientific Journal, ESJ, 2018)
The organizational culture is a critical and coral factor in achieving the dimensions of the administrative creativity. It can be said that the improvement of the practice of organizational culture contributes as an effective factor in the level of administrative creativity in all its dimensions. The organizational culture plays a major role in all levels and activities within the administrative system. It contributes in the creation of the convenient organizational climate, which in turn works on improving and developing the performance in a convenient and efficient manner. It also helps in achieving the individual, collective and organizational objectives that is highlighted through embodiment, development of the modern values, orientations, behavior and standards which work on growth and development of job performance (Alkurdi, 2010). This paper will try to build a theoretical background on the organizational culture and administrative creativity in Saudi Arabia education socity. The main objective is to show the significance of organizational culture and administrative creativity and also the relationship between organizational culture and administrative creativity in universities. This research work showed how the organizational culture is important to the education filed in Saudi Arabia. It contributes in assisting the individual in problem solving and decision making. It helps to make a decisive decision in a relatively record time, and enable to discover problems in order to solve them.